Life Beyond the Home: Nutritional, Occupational, Social and Environmental Predictors of Common Mental Disorders Among Indian Mothers with 6- to 23-Month-old Infants (P11-026-19) - Scott, Samuel (Curr Dev Nutr, 2019)
OBJECTIVES: The mental wellbeing of mothers with young children has been shown to positively affect child development. Little, however, is known about which factors are related to optimal maternal mental health in high poverty rural contexts where women face a broad array of challenges at multiple levels daily. METHODS: Data were from 1644 mother-infant pairs in five Indian states as part of the Women Improving Nutrition through Group-based Strategies study. Common mental disorders (CMD) were assessed through the 20-item Self Reporting Questionnaire. We report on factors spanning nutritional (women's weight, fertility, food security, child illness), occupational (self-reported type of work, time spent in labor, domestic and caretaking activities), social (group membership, decision-making, gender attitudes, household dependents) and environmental (shocks, water, sanitation) aspects of life. Logistic regression models with district controls were used to examine associations between these factors and CMD. RESULTS: On average, women were 26 years old and their children were 15 months old. CMD was present in 262 (16%) of the mothers. Risk factors for CMD included having a failed pregnancy (AOR 1.40, 95% CI 1.01-1.93), and food insecurity (1.13, 1.07-1.20). Protective factors included being engaged in agricultural labor as a main occupation relative to being a housewife (0.20, 0.11-0.35) more time working (AOR associated with 1 more hour of work: 0.88, 0.81-0.97), higher decision-making (0.91, 0.86-0.96), group membership (non-significant trend; 0.76, 0.56-1.02), and having an improved toilet (0.51, 0.35-0.73). CONCLUSIONS: In a sample of rural and mostly tribal Indian households, we found a moderate prevalence of poor mental wellbeing among mothers with young children. We also found that the determinants span a range of factors. Future research should aim to better understand the ways in which working outside the home, albeit in rigorous agricultural work, appears to protect the wellbeing of women in this context. It is plausible that agricultural work mitigates food insecurity, connects women with others and generates income, but these pathways need empirical and ethnographic examination. FUNDING SOURCES: Bill & Melinda Gates Foundation; CGIAR Research Program on Agriculture for Nutrition and Health.